It looks like you've done a great job simplifying the expression and solving for x! I appreciate how you pointed out that the terms were like terms, which made it easier to subtract the coefficients. When you reached the point of isolating x by dividing, it made everything clear. I see that you arrived at x equals six. Nice work!
reply in first person and without numbers to
by Lounise Morissette - Tuesday, 12 November 2024, 9:47 PM
Number of replies: 1
Step 1:
Since 10x−8x10x - 8x10x−8x are like terms (both involve xxx), we can subtract the coefficients:
(10−8)x=12
(10 - 8)x = 12(10−8)x=12
2x=12
Step 2:
To isolate xx divide both sides of the equation by 2:
2x2=122\frac{2x}{2} = \frac{12}{2}22x=212
Simplifying:
x = 6x=6
1 answer